HPSNZ Guidance - COVID-19 Alert Level 4 (2020)
This document provides some guidance from High Performance Sport New Zealand on training and coaching while NZ is at COVID-19 Alert Level 4. It also provides general wellbeing guidelines and information on HPSNZ support services and training facilities.